Men’s Experiences with the Hockey Fans in Training Weight Loss and Healthy Lifestyle Program - Brianne Muise, Stephanie; Gill, Dawn P.; De Cruz, Ashleigh; Riggin, Brendan; Pulford, Roseanne; Sibbald, Shannon L.; Petrella, Robert J. (International Journal of Medical Students, 2016)
Background: Increasing rates of chronic disease, especially in men, have led to an increased effort to implement lifestyle interventions focusing on healthy eating and physical activity. Men are underrepresented in lifestyle programs and some studies have observed that males prefer men-only programs that occur in the context of sports. This paper reviews men’s feedback regarding motivation for joining and overall experience in a 12-week lifestyle intervention in the context of junior level ice hockey teams. Methods: Men age 35-65 with a BMI ?28 were recruited from local ice hockey team fan bases in London and Sarnia Ontario, Canada and randomized to the 12-week lifestyle intervention or control group. Those who attended at least 6 of the 12 weekly sessions, including at least one session in the final six weeks (n=30) were asked to complete an online questionnaire upon finishing the active phase of the intervention. The questionnaire elicited reasons for joining the program, changes seen following their participation, and the usefulness of specific components of the program. Results: For the 27 men who completed the questionnaire, weight loss and a desire to increase physical activity were the two main reasons cited for joining the program. After the intervention, 100% of the men reported eating a healthier diet and 78% increased their activity level. Program satisfaction was high and 96% of men believed both the classroom and exercise components were useful. Conclusion: Our results support previous research showing increased levels of satisfaction in men when lifestyle interventions are run in....